2011
DOI: 10.1016/j.bbadis.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lipid induced insulin resistance: Activated PKCε is a key regulator

Abstract: Fatty acids (FAs) are known to impair insulin signaling in target cells. Accumulating evidences suggest that one of the major sites of FAs adverse effect is insulin receptor (IR). However, the underlying mechanism is yet unclear. An important clue was indicated in leptin receptor deficient (db/db) diabetic mice where increased circulatory FAs was coincided with phosphorylated PKCε and reduced IR expression. We report here that central to this mechanism is the phosphorylation of PKCε by FAs. Kinase dead mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
23
1
1
Order By: Relevance
“…Both classical (PKC␣) and novel (PKC␦) PKC isoforms have been shown to phosphorylate HuR at serine residues within or adjacent to the HuR-nucleo-cytoplasmic shuttling sequence and thereby activate its translocation to the cytoplasm (46,47). Numerous studies have clearly shown that PA treatment activates both the classical and novel class isoforms of PKC (22)(23)(24)48), but the effect of PA on HuR activation is unknown. We have established a connection between PA and HuR and validated the importance of HuR in PA-induced HAMP mRNA stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both classical (PKC␣) and novel (PKC␦) PKC isoforms have been shown to phosphorylate HuR at serine residues within or adjacent to the HuR-nucleo-cytoplasmic shuttling sequence and thereby activate its translocation to the cytoplasm (46,47). Numerous studies have clearly shown that PA treatment activates both the classical and novel class isoforms of PKC (22)(23)(24)48), but the effect of PA on HuR activation is unknown. We have established a connection between PA and HuR and validated the importance of HuR in PA-induced HAMP mRNA stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Independently, PA has also been shown to induce the activation of multiple isoforms of PKC (21)(22)(23)(24)(25). We therefore examined the role of PKC in post-transcriptional regulation of HAMP by PA. For these studies, HepG2 cells were first treated with staurosporine, a potent broad-spectrum protein kinase C inhibitor (39,40).…”
Section: Hamp 3ј-utr Regulation By Are-bp-mentioning
confidence: 99%
See 1 more Smart Citation
“…we found it is F-actin, which has 13 NLS recognizes pPKCε and chaperoned it to nuclear region which coincided with reduced IR expression in skeletal muscle cells [47]. Question is how pPKCε is involved in IR downregulation.…”
Section: Role Of Npkcs In Fa Mediated Insulin Resistancementioning
confidence: 99%
“…We have reported that FA initiates disruption of insulin signal by phosphorylating PKCε in a PDK1 independent manner [21,22,47]. Palmitate and myristate phosphorylated PKCε (pPKCε) which then moves to nuclear region.…”
Section: Role Of Npkcs In Fa Mediated Insulin Resistancementioning
confidence: 99%